Ability to Identify Occupational Health and Safety (OHS) Hazards in Small Sized Enterprises Workers in Cimanggis District, Depok City, West Java - Tarigan, Samuel Peratenta; Ramdhan, Doni Hikmat Hikmat; Nuridzin, Dion Zein; Nugraha, Fajar; Susetyo, Heru (National Journal of Occupational Health and Safety, 2020)
Background: The high number of SMEs players in Depok has an impact on high employment. A large number of workers in SMEs that have not been maximized in applying safety and health aspects in the workplace has the risk of causing several problems such as minor injuries, ergonomic problems, old and insecure equipment, lack of workers' knowledge and poor work environment conditions. Objective: This study aims to assess the ability of workers to recognize OHS hazards in SMEs assisted by Cimanggis District Health Center, Depok City, West Java. Methods: This study used a cross-sectional design carried out on 36 SMEs assisted by Cimanggis Health Center, Depok City, West Java. In each of the selected SMEs, one worker was then interviewed using the ODK Collect application to assess characteristics, knowledge, attitudes, behavior, and assessment of the ability to recognize OHS hazards in SMEs. Results: The results of the study showed that only 41.7% of SMEs were able to recognize OHS hazards properly. In addition, the results show that there are more who have good knowledge (53%), poor attitudes (64%) and bad behavior (61%). Female workers, workers who have working hours of more than 8 hours per day, and SMEs workers with low occupational risks are found to be better in their ability to recognize OHS hazards. Conclusion: The ability to recognize OHS hazards for SMEs workers assisted by Cimanggis District, Depok, West Java is still very slight (under 50%). For this reason, it is necessary to intervene in OHS aspects in SMEs so that these hazards can be minimized